Investigation of powder mixed EDM process parameters for machining Inconel alloy using response surface methodology. (2018) - kumar, Amit; Kumar, Saroj; Mandal, Amitava; Rai Dixit, Amit
Abstract: Powder mixed Electrical discharge machining (PMEDM) is a useful advance machining process for processing difficult to cut conductive materials. Inconel 825 is one of such material which is useful in nuclear power plant, petrochemical, chemical, missileindustries and highly corrosive environment. In this study, machinability of Inconel 825 by Graphenenano powder mixed EDM has been investigated. Three responses parameters namely material removal rate (MRR), surface toughness (SR) and tool wear rate (TWR) have been identified to evaluate process performance. Response surface methodology (RSM)has been used to conduct the experiment. It has been observed that MRR, SR and TWR are mostly influenced by peak current (IP), pulse on time (TON ) and gap voltage (GV).Further, surface morphology of the generated surface has been investigated by taking FESEM images, which shows a comparatively better surface.